The Total Phenolic Content and Antioxidant Activity of Nine Monofloral Honey Types - Chrysoula Tananaki; Maria-Anna Rodopoulou; Maria Dimou; Dimitrios Kanelis; Vasilios Liolios (Applied Sciences, 2024)
Honey is well known for its antioxidant and antimicrobial properties, which significantly contribute to its high demand among consumers. While there is plenty of information available about the antioxidant potential of honey, there is still a lack of research specifically focused on monofloral honeys, as most studies have been based on market samples. To address this issue, in the present study we analyzed the total phenolic content and antioxidant activity of nine monofloral honey types produced in Greece: fir, chestnut, citrus, erica, cotton, Jerusalem thorn, pine, oak and thyme, in comparison with manuka honey. The samples were collected from beekeepers applying the appropriate beekeeping practices. In total, ninety-six representative monofloral honey samples meeting the microscopic, physicochemical, and sensory characteristics were analyzed. Oak honey stood out as the darkest type (L* = 33.67) with the highest total phenolic content (203.75 mg GAE/100 g) and antioxidant activity (106.2 mg AAE/100 g). Chestnut honey closely followed, having also the highest electrical conductivity (1.679 mS/cm). Although manuka honey had a high total phenolic content, its total antioxidant activity was found to be medium-low compared to fir, pine, and erica honeys. Citrus honey, being the lightest in color (L* = 37.2), exhibited the lowest total antioxidant activity (6.36 mg AAE/100 g). Statistical analysis revealed significant positive correlation between total antioxidant activity and electrical conductivity (ra-e = 0.587, pa-e = 0.000), and negative correlation between total antioxidant activity and L* parameter (ra-L = −0.424, pa-L = 0.000). Similar correlations were also observed regarding total phenolic content (rp-e = 0.457, pp-e = 0.000, rp-L = −0.455, pp-L = 0.000). In conclusion, oak and chestnut honeys seem to have a high antioxidant potential, that should be further explored, to highlight their value and help promote them worldwide.